Structure of HgBa2CuO4+delta (0.06 - Balagurov, A; Sheptyakov, D; Aksenov, V; Antipov, E; Putilin, SN; Radaelli, P; Marezio, M (1999)
The results of a neutron-diffraction study of the HgBa2CuO4+δ structure at ambient pressure and under external pressure at different extra oxygen concentrations are presented. The results have been analyzed together with the data of previous investigations. It is shown that in the cation-stoichiometric samples the Oδ oxygen is only present in the center of the mercury layer, Tc is parabolically dependent on δ, and Tc,max is obtained at δopt=0.13±0.01. The influence of pressure on the structure strongly depends on the doping level. At low oxygen content (δ≈0.06), the compression of the structure is practically uniform. An increase of the extra oxygen content to 0.19 (overdoped state) results in the larger compression of the apical Cu-O(2) and Ba-Oδdistances, while the HgO2 dumb-bell as well as the distance between Ba and O belonging to the (CuO2) layer become practically pressure independent. These results are in agreement with models, in which the effect of the charge transfer from the reservoir to the (CuO2) layers does not play a dominant role in the Tc increase with pressure at low and optimal δ values, while in the overdoped state the charge transfer is enhanced under pressure, thus inducing the Tc decrease. © 1999 The American Physical Society.